2018
DOI: 10.28991/cej-030964
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of Post-Tensioned Two-Way Concrete Slabs under Flexural Loading

Abstract: Post-Tensioned (PT) method is a widely used technique to prevent cracking and to minimize the deflection which is resulted by loads. In this method, stress is applied after concrete placing and reach adequate hardening and strength. This paper investigates the structural behaviour of PT two-way concrete slabs. The main objective of this study involves a detailed flexural behavior analytical investigation of PT concrete two-way slab with the different bonded tendon layout. This will be achieved by non-linear Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Bridge Analysing Program at the Cambridge University [7] for assessing the reserve strength in bridges is suggestive of its applicability for practical design reasons. Ali K. Hussein et al [8] investigated the response of a posttensioned bi-directional slab to bending using various tendon configurations. Nineteen distinct post-tensioned concrete slab models were the subject of a parametric analysis, which revealed that the load-bearing capability of slab with tendons inserted in two directions is higher than that in which tendons inserted in uni direction in slab.…”
Section: Introductionmentioning
confidence: 99%
“…Bridge Analysing Program at the Cambridge University [7] for assessing the reserve strength in bridges is suggestive of its applicability for practical design reasons. Ali K. Hussein et al [8] investigated the response of a posttensioned bi-directional slab to bending using various tendon configurations. Nineteen distinct post-tensioned concrete slab models were the subject of a parametric analysis, which revealed that the load-bearing capability of slab with tendons inserted in two directions is higher than that in which tendons inserted in uni direction in slab.…”
Section: Introductionmentioning
confidence: 99%
“…Abdul-Razzaq et al [19] studied the behavior of posttensioned two way slab under flexure. Parametric study carried out by the author reveals that moment carrying capacity of the slabs having tendons placed in two directions is more than slabs having tendons in one direction.…”
Section: Introductionmentioning
confidence: 99%
“…Abdul-Razzaq et al [19] studied the behavior of post-tensioned two way slab under flexure with different layouts of tendons. Parametric study was conducted on nineteen different post-tensioned concrete slab models and shows that load carrying capacity of the slab having tendons placed in two directions is greater than tendons placed in one direction.…”
Section: Introductionmentioning
confidence: 99%